1987
DOI: 10.2165/00003495-198734010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline

Abstract: Pentoxifylline (oxpentifylline) is an orally active haemorheological agent for the treatment of peripheral vascular disease, cerebrovascular disease and a number of other conditions involving a defective regional microcirculation. Pentoxifylline acts primarily by increasing red blood cell deformability, by reducing blood viscosity and by decreasing the potential for platelet aggregation and thrombus formation. Extensive open and placebo-controlled studies have shown that pentoxifylline 600 to 1200 mg/day for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 887 publications
(84 citation statements)
references
References 117 publications
0
84
0
Order By: Relevance
“…Pentoxifylline exhibits anti-inflammatory properties by inhibiting the aggregation of neutrophils and thrombocytes, the movement and chemotaxis of polymorphonuclear cells, and blood viscosity [12,59,60]. Pentoxifylline reduces the number of neutrophils that adhere to the vascular endothelium and their transendothelial transport [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline exhibits anti-inflammatory properties by inhibiting the aggregation of neutrophils and thrombocytes, the movement and chemotaxis of polymorphonuclear cells, and blood viscosity [12,59,60]. Pentoxifylline reduces the number of neutrophils that adhere to the vascular endothelium and their transendothelial transport [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, thalidomide is not easily available, associated with dose-related neuropathy and usage in women is restricted [12]. Pentoxifylline (PTX) is a substituted methylxanthine approved for the treatment of intermittent claudication and other conditions involving defective regional microcirculation [13]. Besides its hemorheologic activity, PTX has been found to suppress the production of TNF-α by murine and human leukocytes [14, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several lines of studies have also provided evidence showing potential advantages for the combination of tRA with PTX. The reasons include (1) PTX could block cytokine induction and inhibit inflammatory leukocyte infiltration [38, 39], and thus inhibit the retinoic acid syndrome; (2) PTX given by the oral route has a widely safe therapeutic range [40], and oral administration of tRA is more potent than the parental route [41]; (3) PTX which could inhibit the interaction of leukocytes with endothelial cells [21, 22] may decrease the pulmonary leakage syndrome; (4) PTX, which could inhibit activation of coagulation and fibrinolysis induced by endotoxin [42], may further decrease the possibility of coagulopathies in patients with APL; (5) PTX which could improve postirradiation wound healing [43], decreases bone marrow transplantation- and chemotherapy-induced untoward reactions [44], and fortifies patients with malignancy-associated anorexia and cachexia [45], may promote the well-being of patients with tRA treatment who commonly exhibit dryness of skin, mucositis and headache. Thus, it may be worthwhile to further evaluate the effects of the combination of PTX with tRA simply given via oral route as induction therapy in patients with APL.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effect of circulation on the PTX is believed to be due to the attenuation of the postischemic hyperemia and increment of erythrocyte deformability [20, 21]. Several studies have also shown that PTX could inhibit the interaction of leukocytes with endothelial cells in vascular leakage syndrome and leukocyte inflammatory responses [22].…”
Section: Introductionmentioning
confidence: 99%